Acute renal failure and hypoglycaemia due to sulphadiazine poisoning. Issue 616 (February 1977) - Craft, A. W.; Brocklebank, J. T.; Jackson, R. H.
Abstract : A 3-year-old girl is described who became oliguric and hypoglycaemic whilst receiving an excessive dose of sulphadiazine. The mechanism of the hypoglycaemia is discussed.